Применение β-фруктофуранозидазы в производстве спирта - Суходол, Виктория Фоминична; Куц, Анатолий Михайлович; Добролинская, Г. М.; Почикаева, Н. Н. (My University, 1977)
Исследовали влияние препарата Фруктаваморин Г10х на процесс сбраживания мелассного сусла, накопление спирта, биомассы, вторичных и побочных продуктов брожения. Установлено, что применение препарата Фруктаваморин Г10х повышает выход спирта на 0,4 дал из 1 т условного крахмала за счет более полного выбраживания сахаров мелассы. Experiments were carried out to study the effect of the preparation Fructawamorin Gl0x on the fermentation of molasses wort and accumulation of alcohols, biomass, se¬condary and side fermentation products. The use of Fructawamorin GlOx increased the alcohol yield by 0,4 decalitres dal per 1 ton of comparison starch to occur due to a more complete fermentation of molasses sugars.
Keywords: дріжджові клітини; выход спирта; сбраживание мелассного сусла; дрожжевые клетки; рreparation Fructawamorin GlOx; побочные продукты брожения; fermentation of molasses wort; fermentation by-products; yeast cells; out alcohol; кафедра біотехнології продуктів бродіння і виноробства